2006
DOI: 10.1381/096089206778026343
|View full text |Cite
|
Sign up to set email alerts
|

Early Gastric Cancer found at Preoperative Assessment for Bariatric Surgery

Abstract: An association between gastric cancer and obesity has been suggested in large epidemiologic series. We present a 61-year-old lady with BMI 48.7 kg/m2, who underwent preoperative work-up for Roux-en-Y gastric bypass. Her endoscopy showed a depressed lesion at the incisura angularis, suggesting early gastric cancer. The biopsy confirmed well/moderately-differentiated adenocarcinoma. The surgical approach was subtotal gastrectomy leaving only part of the fundus, and was performed on an oncological basis, with lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…Different studies report gastric cancer after bariatric surgery, but only a few report this as a BMI Body mass index preoperative finding. Seva-Pereira et al [26] and Boru et al [27] had previously reported one case of early gastric cancer during preoperative assessment for bariatric surgery. Barrett's esophagus has also been reported in previous studies; Boru et al [27] confirm Barrett's esophagus in one female patient (0.16%), Zeni et al [25] report two patients (1.3%) with Barrett's esophagus in a cohort of 159 patients, neither of whom had dysplasia, and Azagury et al [19] found one patient (0.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Different studies report gastric cancer after bariatric surgery, but only a few report this as a BMI Body mass index preoperative finding. Seva-Pereira et al [26] and Boru et al [27] had previously reported one case of early gastric cancer during preoperative assessment for bariatric surgery. Barrett's esophagus has also been reported in previous studies; Boru et al [27] confirm Barrett's esophagus in one female patient (0.16%), Zeni et al [25] report two patients (1.3%) with Barrett's esophagus in a cohort of 159 patients, neither of whom had dysplasia, and Azagury et al [19] found one patient (0.6%).…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, gastric banding is the most frequently performed bariatric operation. The risk of esophageal and gastric cancer, especially after restrictive procedures, has only been reported in case reports and in one review [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…15 Malignancy may be uncommon but if suspected needs additional evaluation. 16 Performance of a sleeve gastrectomy in the presence of a hiatal hernia and/or gastroesophageal reflux is controversial. Some studies have reported exacerbation of gastroesophageal reflux disease in some or de novo reflux in others, whereas some have reported not much influence on gastroesophageal reflux disease.…”
Section: Discussionmentioning
confidence: 99%